Differential calculus and its applications - Field, Mike (Mineola, N.Y. : Dover Publications, 2012)
" This text offers a synthesis of theory and application related to modern techniques of differentiation. Based on undergraduate courses in advanced calculus, the treatment covers a wide range of topics, from soft functional analysis and finite-dimensional linear algebra to differential equations on submanifolds of Euclidean space. 1976 edition"--
Originally published: New York : Van Nostrand Reinhold, 1976.
Includes bibliographical references and index.
Keywords: Differential calculus; MATHEMATICS / Calculus